2020
DOI: 10.1186/s13071-020-04199-8
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus granulosus (sensu stricto) (G1, G3) and E. ortleppi (G5) in Pakistan: phylogeny, genetic diversity and population structural analysis based on mitochondrial DNA

Abstract: Background Cystic echinococcosis (CE) is a serious tapeworm infection caused by Echinococcus granulosus ( sensu lato ) which infects a wide range of animals and humans worldwide. Despite the millions of livestock heads reared in Pakistan, only a few reports on CE prevalence and even fewer on the genetic diversity are available for the country. Meanwhile, the available reports on the genetic diversity are predominantly based on short sequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…In this study, 75% (3/4) of hydatid cysts found in camels with G5 genotype were fertile, whereas G5 in goats and cattle were infertile. The result concerning the G5 genotype showing no fertility in cattle agrees with the study conducted in Pakistan [81]. However, Monteiro et al [82] reported the frequency of 43.4% G5 genotype for fertile cysts in the lung of cattle in Brazil.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, 75% (3/4) of hydatid cysts found in camels with G5 genotype were fertile, whereas G5 in goats and cattle were infertile. The result concerning the G5 genotype showing no fertility in cattle agrees with the study conducted in Pakistan [81]. However, Monteiro et al [82] reported the frequency of 43.4% G5 genotype for fertile cysts in the lung of cattle in Brazil.…”
Section: Discussionsupporting
confidence: 85%
“…The nucleotide sequence data reported in this paper are available in the GenBank™ database under the following accession numbers: MZ322608—MZ322609. To estimate the phylogenetic position of the Polish isolate, homologous mitochondrial DNA sequences described earlier [ 8 , 29 , 32 , 33 , 34 , 36 , 37 , 52 , 58 , 59 , 60 , 61 , 62 ] were retrieved from GenBank and used in the analyses (GenBank accession numbers were presented in Figure 3 and Figure 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…Parasites are capable of causing an acute, chronic, and debilitating type of diseases (3)(4)(5)(6). In nature, parasitic protozoa may be found almost everywhere.…”
Section: Introductionmentioning
confidence: 99%